PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN SENI RUPA MENGGUNAKAN MODEL PROJECT BASED LEARNING (PjBL) DI KELAS V SDN 07 BELAKANG BALOK KOTA BUKITTINGGI - Hilmia Hidjriani; Mansurdin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by the low learning outcomes of students, the learning process has not been centered on students, this can be seen from the low creativity of students in learning so that this makes students less able to develop the learning that is carried out. The purpose of this study was to describe the learning outcomes of students in learning fine artqqs using the Project Based Learning model. The approach used is a qualitative and quantitative approach. The type of research used in this research is classroom action research (PTK) which is carried out in two cycles. Each cycle includes four stages, namely planning, implementation, observation, and reflection. The subjects of this research were teachers and fifth grade students totaling 28 people. The results showed an increase in: 1) The first cycle teaching module evaluation received an average of 86.1% with good qualifications (B) and the second cycle received an average of 97.2% with very good qualifications (SB), 2) Teacher involvement in the first cycle got an average of 78.13% with sufficient qualifications (C), and the second cycle got an average of 95.8% with very good qualifications (SB), 3) Learner involvement in the first cycle got an average of 79.14% with sufficient qualifications (C) and the second cycle got an average of 89.5% with good qualifications (B), 4) Assessment of learning outcomes in the first cycle averaged 74.5% with sufficient qualifications (C) and the second cycle averaged 84.4% with good qualifications (B). Thus learning fine arts using a project-based learning model can improve student learning outcomes.